Lentiviral reporter constructs for fluorescence tracking of the temporospatial pattern of Smad3 signaling - Christina H. Stuelten; Anil K. Kamaraju; Lalage M. Wakefield; Anita B. Roberts (BioTechniques, 2007)
Canonical TGF-β is involved in cell differentiation, tissue maintenance, and wound healing, but also plays a central role in the pathogenesis of diseases such as cancer. Here we describe a lentivirus-based reporter vector system expressing green fluorescent protein (GFP) or red fluorescent protein (RFP) under the control of a Smad3-responsive element (CAGA)12 that allows observation of the temporospatial pattern of endogeneous Smad3-mediated signaling on a cellular level. Use of this method will be valuable to identify cells with active Smad3 signaling and investigate the role of endogenous Smad3 signaling in complex systems such as co-cultures in vitro, or in tumors during tumor cell invasion and metastasis in vivo.